Anti‐allergic Effect of Pleuran (β‐glucan from Pleurotus ostreatus) in Children with Recurrent Respiratory Tract Infections. (7th June 2013) - Jesenak, Milos; Hrubisko, Martin; Majtan, Juraj; Rennerova, Zuzana; Banovcin, Peter
<x xml:space="preserve">Abstract</x> Recurrent respiratory tract infections (RRTIs) present a very important problem in paediatric praxis. As true immunodeficiencies are rare, one of the most important factors assumed to contribute to increased respiratory morbidity is atopy. Several preparations of natural origin have been used for the prevention of RRTIs, and some of the most effective immunomodulators are biologically active polysaccharides – e.g. ß‐glucans. In our randomised, double‐blind, placebo‐controlled study, we investigated the prevalence of atopy in a group of children with RRTIs and the potential anti‐allergic effect of pleuran (ß‐glucan isolated from Pleurotus ostreatus) on basic laboratory markers of allergic inflammation. We confirmed that atopy may be an important factor contributing to the increased respiratory morbidity in children with RRTIs. The active treatment with pleuran resulted in a significant reduction of peripheral blood eosinophilia and stabilised the levels of total IgE in serum. This was more evident in atopic subjects. Pleuran showed a potential anti‐allergic effect. This previously non‐described effect could expand the application of this natural immunomodulator also as a complementary adjuvant therapy in allergic patients. Copyright © 2013 John Wiley & Sons, Ltd.